MRI parameters predict central lumbar spinal stenosis combined with redundant nerve roots: a prospective MRI study - Qian, Jingli; Liang, Kaiwen; Luo, Xianping; Ying, Caiyun (Frontiers in Neurology, 2024)
Background To observe changes in the cauda equina nerve on lumbar MRI in patients with central lumbar spinal stenosis (LSS). Methods 878 patients diagnosed with LSS by clinical and MRI were divided into the redundant group (204 patients) and the nonredundant group (674 patients) according to the presence or absence of redundant nerve roots (RNRs). The anteroposterior diameter of the spinal canal (APDS) and the presence of multiple level stenosis, disc herniation, thickening of ligamentum flavum (LF) and increased epidural fat were assessed on MRI. Univariate and multivariate logistic regression analyses were performed to explore the predictors of LSS combined with RNRs. Results Patients with LSS combined with RNRs had thicker epidural fat, smaller APDS and more combined multifaceted stenosis. Female patients and older LSS patients were more likely to develop RNRs; there was no difference between two groups in terms of disc herniation (p > 0. 05). Age, APDS, multiple level stenosis, and increased epidural fat were significantly correlated with the formation of LSS combined with RNRs (p < 0.05). Conclusion A smaller APDS and the presence of multiple level stenosis, thickening of LF, and increased epidural fat may be manifestations of anatomical differences in patients with LSS combined with RNRs. Age, APDS, multiple level stenosis, and increased epidural fat play important roles. The lumbar spine was measured and its anatomy was observed using multiple methods, and cauda equina changes were assessed to identify the best anatomical predictors and provide new therapeutic strategies for the management of LSS combined with RNRs.